Pengaruh Work Life Balance, Lingkungan Kerja, dan Motivasi Kerja terhadap Organizational Citizenship Behavior: Studi pada Karyawan PT Gogomedia Visindo, Tangerang - Farah Isnaeni Apriliyana; Zulvia Khalid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Organizational Citizenship Behavior (OCB) plays a vital role in supporting organizational effectiveness and efficiency, as it reflects employees’ voluntary behaviors that go beyond formal job responsibilities and contribute to overall organizational performance. Therefore, it is important for organizations to understand the factors that can enhance OCB among their employees. This study aims to analyze the influence of Work-Life Balance, Work Environment, and Work Motivation on Organizational Citizenship Behavior at PT Gogomedia Visindo Tangerang. The research employed a quantitative approach with a sample of 100 respondents selected through non-probability sampling using a snowball sampling technique. Data were collected through questionnaires measured on a Likert scale and analyzed using Microsoft Excel 2021 and SPSS version 22. The data analysis methods included correlation tests and multiple linear regression analysis to examine both the relationships and effects among the variables. The results indicate that Work-Life Balance, Work Environment, and Work Motivation have a positive and significant influence on Organizational Citizenship Behavior, both partially and simultaneously. This finding suggests that better work-life balance, a supportive work environment, and higher motivation levels encourage employees to demonstrate stronger OCB. The study emphasizes the strategic importance of organizational initiatives that foster employee well-being, provide conducive working conditions, and maintain high levels of motivation. By doing so, organizations can strengthen employee commitment, maximize contributions, and enhance long-term organizational performance.